Seismic Stratigraphy of Pleistocene Deltaic Deposits in Bahía Blanca Estuary, Argentina - Aliotta, Salvador (2014)
The Bahía Blanca estuary (Argentina) has a morphological configuration resulting from hydrological and sedimentary processes related to Late Quaternary sea level changes. This estuarine system occupies a large coastal plain with a dense net of tidal channels, low-altitude islands and large intertidal flats. Little is known about the sedimentary units of the marine subbottom. Therefore, a stratigraphical analysis of the northern coast of Bahía Blanca estuary was carried out using high resolution seismic (3.5 kHz) in order to: i) define Quaternary sequences, ii) describe sedimentary structures, and iii) determine the paleoenvironmental conditions of sedimentation. The seismic stratigraphic data collected and their correlation with drilling lithological data show five seismic sequences (S1, S2, S3, S4 and S5), of which S1-S2 were found to be associated with a continental paleoenvironment of Miocene-Pleistocene age. Sequences S3 and S4, whose lithology and seismic facies (paleochannel structures and prograding reflection configurations), were defined on these materials, to evidence the development of an ancient deltaic environment which was part of a large Pleistocene drainage system. The S5 sequence was formed during the Holocene transgressiveregressive process and complete the seismostratigraphic column defined in the present study.